(untitled) (AFRICAN JOURNAL OF APPLIED RESEARCH, 2025)
Purpose: This study utilises historical cost data of priced bills of quantities to analyse the cost breakdown of new public building projects in Ghana as a case study in preliminary cost estimating. Leaning on relevant conceptual/theoretical frameworks, the study analyses the distribution of costs (i.e., direct costs of measured works and project allowances) in a typical work section bill of quantities. Design/Methodology/Approach: The study adopted a quantitative research approach. A total of 367 SMM5- and SMM7-based work section bills of quantities obtained from public quantity surveying firms were used for the study. The data was organised in Microsoft Excel and analysed in Stata using descriptive statistics. Research Limitation: The study was limited to 367 bills of quantities from SMM5 and SMM7-based work sections, which may not fully represent the entire spectrum of quantity surveying practices across different project types, scales, and geographic regions. Findings: Mean and median values of the analysis show that, for both SMM5 and SMM7, substructure and finishes constitute the two cost-significant measured works in order of in magnitude. For project allowances, preliminaries, and contingency sums, averages 6% and 8% in both SMM5 and SMM7 projects, while provisional sums constitute about 11% in SMM5 projects but 2% in SMM7 projects. Consultancy fees is approximately 8%, but can reach a maximum of 16%. The observed significant gap in provisional sum in SMM5 and SMM7 bills of quantities sheds light on efficiency in cost estimate build-up resulting from the effectiveness of the Standard Method of Measurement (SMM7) as an instrument of measurement. Practical implication: The study’s results provide valuable insights for quantity surveyors during cost evaluation, budgeting, and planning of new building projects. Social Implication: This improved cost predictability has significant social benefits, including better allocation of public resources, reduced burden on taxpayers, and enhanced delivery of essential infrastructure such as schools, hospitals, roads, and housing projects that serve community needs. Original value: The study grounds a useful but otherwise intuitive professional practice in theory and supports this with empirical data.